Sexual Politics and State’s Indifference to Sexual Violence in Indonesia - Irawaty, Diah (Yayasan Jurnal Perempuan, 2016)
How does not the government that represents the state show a strong commitment and responsibility to ending sexual violence? Why does the state choose to engage more in giving “temporary response” to the cases of sexual violence? If the state appears to play a systematic role in ending sexual violence, why does not the agenda really address patriarchal structure as the root of sexual violence? This article discusses how the state’s politics of sexuality in Indonesia that was mainly propagated during the New Order administration plays a pivotal role in the irresponsible way the state and the society deal with sexual violence.